Influence of Early Life Lead (Pb) Exposure on α-Synuclein, GSK-3β and Caspase-3 Mediated Tauopathy: Implications on Alzheimer's Disease - Bihaqi, Syed W.; Alansi, Bothaina; Masoud, Anwar M.; Mushtaq, Foqia; Subaiea, Gehad M.; Zawia, Nasser H. (Current Alzheimer Research, 2018)
Background: Previously we have shown that developmental exposure to the heavy metal lead (Pb) resulted in latent cognitive impairment, upregulation of biomarkers and pathology associated with both the tau and amyloid pathways, however, the impact on Alpha Synuclein (α-Syn) and its relationship to these pathways and their connection to cognitive performance warrant further elucidation. Objective: The present study determined the impact of developmental Pb exposure on the α-Syn pathways in a mouse model knock-out (KO) for murine tau gene and in differentiated human neuroblastoma SHSY5Y cell line exposed to a series of Pb concentrations. Methods: Western blot analysis and RT-PCR were used to assess the levels of intermediates in the tau and α-Syn pathways following postnatal Pb exposure on aged mice lacking tau gene and in differentiated SHSY5Y cells on day 3 and day 6 after the Pb exposure had ceased. Result: Early life Pb exposure is accompanied by latent up-regulation in α-Syn in these mice. Furthermore, prior exposure to Pb in-vitro also resulted in an increase in α-Syn, its phosphorylated forms, as well as an increase in glycogen synthase kinase 3β (GSK-3β) and Caspase-3. Conclusion: An environmental agent can act as a latent inducer of both α-Syn and associated kinases that are involved in tau hyperphosphorylation and may allude to the interactive nature of these two neurodegenerative pathways.
Keywords: Alzheimer' s disease